Protein malnutrition impairs bone marrow endothelial cells affecting hematopoiesis. Issue 5 (May 2020) - Hastreiter, Araceli Aparecida; Galvão dos Santos, Guilherme; Cavalcante Santos, Ed Wilson; Makiyama, Edson Naoto; Borelli, Primavera; Fock, Ricardo Ambrósio
Summary: Background & aims: Protein malnutrition (PM) affects hematopoiesis leading to bone marrow (BM) hypoplasia and arrests hematopoietic stem cells (HSC) in G0 /G1 cell cycle phases, which cause anemia and leukopenia. Hematopoiesis is mainly regulated by BM niches where endothelial cells (EC) present a key regulatory role. Thus, our objective is to evaluate whether PM affects the modulatory capacity of EC on hematopoiesis. Methods: C57BL/6 male mice received for 5 weeks a normal protein diet (12% casein) or a low protein diet (2% casein). MSC were isolated and differentiated in vitro into EC and the synthesis of SCF, Ang-1, CXCL-12, IL-11, TGF-β and G-CSF were evaluated. The HSC and hematopoietic progenitors were quantified and the EC capacity to modulate the hematopoietic system was also evaluated. Moreover, the ability of PM bone marrow to support hematopoieisis was assessed by proliferation of infused leukemic myelo-monoblasts cells. Results: PM decreases HSC and hematopoietic progenitor pool and promotes cell cycle arrest and a lower proliferation rate of leukemic myelo-monoblasts. PM also committed hematopoietic regulatory characteristics from EC, resulting in the modification of both cell cycle pattern and hematopoietic differentiation. Conclusion: BM microenvironment is compromised in PM, and since PM disturbs EC, it becomes one of the factors responsible for the hematopoietic cell cycle arrest and impairment of HSC differentiation.